1999
DOI: 10.1038/sj.onc.1202479
|View full text |Cite
|
Sign up to set email alerts
|

The presence of the Rb c-box peptide in the cytoplasm inhibits p210bcr-abl transforming function

Abstract: In order to test if the carboxyl terminal polypeptide of the Retinoblastoma (Rb) tumor suppressor protein, could be used to suppress the growth factor-independent growth phenotype of p210 bcr-abl positive myeloid cells, we introduced a truncated form of the 3' end of the Rb cDNA encoding its last 173 amino acid residues (Rb Cbox) which localize into the cytoplasm where the p210 bcr-abl transforming protein is found, into myeloid cells (32D) which depends on the p210 bcr-abl protein for IL3 growth factor-indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Disease progression in CML is accompanied by an increase in the level of Bcr-Abl mRNA (Gaiger et al, 1995;Elmaagacli et al, 2000) and protein (Guo et al, 1991). Due to the heterogeneity of primary cells from patients, it is difficult to isolate the cell signaling pathways that are affected by Bcr-Abl and are the most important for blastic transformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disease progression in CML is accompanied by an increase in the level of Bcr-Abl mRNA (Gaiger et al, 1995;Elmaagacli et al, 2000) and protein (Guo et al, 1991). Due to the heterogeneity of primary cells from patients, it is difficult to isolate the cell signaling pathways that are affected by Bcr-Abl and are the most important for blastic transformation.…”
Section: Discussionmentioning
confidence: 99%
“…In CML, not only does the BCR-ABL oncogene persist throughout the course of the disease, but its expression, as assessed by mRNA (Gaiger et al, 1995;Lin et al, 1996;Elmaagacli et al, 2000) or protein (Guo et al, 1991), increases with disease progression. Consequently, any phenotypic abnormalities caused by BcrAbl will be dose dependent with subtle effects tending to become extreme as expression increases over time.…”
Section: Introductionmentioning
confidence: 99%
“…67,68 Accordingly, the exclusively cytoplasmic localization of BCR-ABL1 may allow it to escape the modulatory effect of intranuclear proteins such as retinoblastoma (Rb) tumor suppressor which negatively regulates ABL1. 69 Moreover, BCR-ABL1 demonstrated more abundant binding and modification of actin microfilaments than ABL1, which plays an important role in leukemogenesis. 70 Considering their opposite, pro-and antioncogenic properties, the BCR-ABL1-to-ABL1 ratio may play a key role in shaping the ultimate malignant features of the BCR-ABL1-transformed cells.…”
Section: /2mentioning
confidence: 99%
“…It has been reported that Rb is an upstream negative regulator of Abl tyrosine kinase (Guo et al, 1999;Wang, 2000). To explore whether Rb is a substrate of Abl and serves as a downstream effector of Abl, Nterminal (Rb-N), A/B pocket (Rb-A/B), and C-terminal (Rb-C) domains of Rb were expressed in bacteria with a GST tag and subjected to an in vitro kinase assay.…”
Section: Tyrosine Phosphorylation Of Rb By Abl Tyrosine Kinasementioning
confidence: 99%
“…Bcr/ Abl activates a number of cytoplasmic signal transduction pathways that are normally controlled by receptor tyrosine kinases (Druker et al, 2001), while the downstream effectors of Bcr/Abl are not well understood. The C-terminal domain of Rb binds the kinase domain of Abl and inhibits its catalytic activity (Guo et al, 1999;Wang, 2000), and thus Rb is considered to be an upstream negative regulator of Abl. However, the physiological link between Rb and Abl in cancer cells still remains obscure.…”
Section: Introductionmentioning
confidence: 99%